Jaka przyszłość czeka muzeum archeologiczne? Dyskusja z tezami zawartymi w książce Moniki Stobieckiej: Natura artefaktu, kultura eksponatu. Projekt krytycznego muzeum archeologicznego - Pawleta, Michał (Folia Praehistorica Posnaniensia, 2021)
This article is of polemical nature. It discusses main theses of the recently published book by Monika Stobiecka: Natura artefaktu, kultura eksponatu. Projekt krytycznego muzeum archeologicznego (2020). The book presents contemporary archaeology as a very innovative discipline striving for interdisciplinarity and extending beyond traditional research issues and borders. At the same, the authoress postulates a need to reorient archaeology and create a new type of archaeological museum, namely critical museum – “museum of life”.